Novel combined sonochemical/solvothermal syntheses, characterization and optical properties of CdS nanorods - Anukorn Phuruangrat (2018)
The combined sonochemical/solvothermal syntheses were developed to synthesize nanostructured materials. In this research, the Cd(NO 3 ) 2 .4H 2 O and (NH 4 ) 2 S chemicals were dissolved in ethylenediamine, sonicated for 1-5h under ultrasonic radiation and followed by the solvothermal synthesis at 200°C for 24h. The products were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), high resolution transmission electron microscopy (HRTEM), selected area electron diffraction (SAED), UV-visible (UV-vis) spectrometry and Raman spectroscopy. The analyses showed pure phase of hexagonal CdS uniform nanorods. To achieve 1-3μm long and 20-30nm diameter nanorods, the process was done by the 5h ultrasonic route combined with the 200°C and 24h conventional solvothermal reaction. These nanorods became the mixture of nanoparticles, nanorods and microrods when the solution mixture was processed by only the conventional solvothermal method. In addition, the absorption peak of the long nanorods was detected at 487nm. © 2012 Elsevier B.V.